Tax-benefit microsimulation modelling in Zanzibar: A feasibility study - Vincent Leyaro; Faith Masekesa; Ramadhan Ramadhan; Elineema Kisanga; Michael Noble; Gemma Clare Wright (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This working paper explores the feasibility of developing a tax and benefit microsimulation model in Zanzibar using the EUROMOD microsimulation software. We review Zanzibar's tax and benefit arrangements and the potential household survey dataset that would underpin the model, and we conclude that such a model would be feasible for Zanzibar. It would complement the TAZMOD model for Tanzania Mainland, enabling harmonized analysis using a common platform across the United Republic of Tanzania as well as with other SOUTHMOD country models.
Keywords: E62; H24; I38; 330; tax; benefits; microsimulation; Zanzibar